Pelatihan Pembuatan Pakan Ternak Fermentasi Di Dusun Layonga Galung Desa Batulaya Kabupaten Tinambung Sulawesi Barat - Reski Praja Putra; Indrayani; Nur Rahmah; Andi Muhammad Akram Mukhlis; Andi Alamsyah Rivai (Vokatek: Jurnal Pengabdian Masyarakat, 2023)
Layonga Galung is one of the hamlets in Batulaya Village, Tinambung District, one of the sub-districts in Polewali Mandar Regency, West Sulawesi. The first stage of this service activity is conducting observations. Through observations, the people in Layonga Galung Hamlet know to work as livestock breeders and farmers. The public hopes information about animal feed can increase the productivity of livestock, cattle and goats. The solution to the problem offered in this activity is making fermented animal feed. Activities are carried out through counseling methods and providing materials, demonstrations, mentoring, and evaluation. The main ingredients used are leaves and plants, it has been used as animal feed in this village. Diluted brown sugar is used as a carbon source for Probio-7 microbes. The fermentation process was microaerophilically using a tarpaulin or bucket as a fermentation container, fermentation is carried out for two weeks. Based on the evaluation, the community in Layonga Galong Hamlet has been able to make fermented animal feed independently.